The law of one price in equity volatility markets - Peter Van Tassel (Federal Reserve Bank of New York, 2020)
This paper documents law of one price violations in equity volatility markets. While tightly linked by no-arbitrage restrictions, the prices of VIX futures exhibit significant deviations relative to their option-implied upper bounds. Static arbitrage opportunities occur when the prices of VIX futures violate their bounds. The deviations widen during periods of market stress and predict the returns of VIX futures. A relative value trading strategy based on the deviation measure earns a large Sharpe ratio and economically significant alpha-to-margin. There is evidence that systematic risk and demand pressure contribute to the variation in the no-arbitrage deviations over time.
Keywords: G12; G13; C58; 330; limits-to-arbitrage; VIX futures; variance swaps; volatility; return predictability